Precautionary Principle dalam Penghitungan Pemulihan Kerusakan Lingkungan Hidup Akibat Kebakaran Hutan dan Lahan (RechtJiva, 2024)
This research was conducted because there is a high number of environmental crimes committed by corporations, especially land and forest fires. One of the cases of forest and land fires that often occur is due to corporate activities in the field of oil palm plantations. There are five decisions related to forest and land fires analyzed, in these decisions the analysis will focus on additional punishment in the form of environmental damage recovery costs. The calculation of the cost of restoring environmental damage will be linked to the precautionary principle. This research was conducted to find out whether the panel of judges in handling criminal cases of forest and land fires had applied the precautionary principle, what was the ratio decidendi in applying the principle, and whether the application was in accordance with the UUPPLH and KKMA P3LH. The research was conducted using the normative juridical method and used a statutory, conceptual, and case approach. The results showed that not all forest and land fire criminal cases, especially in calculating additional criminal costs, require the application of the precautionary principle. The judges who apply the precautionary principle are of the view that the decline in environmental quality cannot fully return, the application is also based on the results of laboratory analysis and expert opinions. The application of the precautionary principle can refer to the UUPPLH and KKMA P3LH. In the five decisions analyzed, the precautionary principle applied by the judges based on these two regulations was not all of its elements fulfilled.